Nitrogen and Phosphorus Changes in Soil and Soil Water after Cultivation - Mark Watkins; Hayley Castlehouse; Murray Hannah; David M. Nash (Applied and Environmental Soil Science)
Untilled dairy pasture has the potential to release more phosphorus to the environment than a regularly ploughed pasture. In this paper we report the initial results of a study comparing the effects of cultivation, phosphorus (P) fertiliser (10, 35, and 100 kg P/ha), and two types of vegetation (ryegrass (Lolium perenne) or ryegrass mixed with clover (Trifolium repens)) in a randomised complete block design. Phosphorus was measured in soil samples taken from depths of 0–20 mm and 0–100 mm. Waters extracted from the 0–20 mm samples were also analysed. In all cases, the P concentrations (Olsen P, Colwell P, Total P, CaCl2 extractable P, Dissolved Reactive P, and Total Dissolved P) in the top 20 mm declined with ploughing. Dissolved Reactive P measured in the soil water was 70% less overall in the ploughed plots compared with the unploughed plots, and by 35 weeks after P treatments the decrease in Dissolved Reactive P was 66%. The effects of the fertiliser and pasture treatments were inconclusive. The data suggest that ploughing can lower the risk of P exports from intensive dairy farms in the trial area.